2008
DOI: 10.1074/jbc.m706710200
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon Consensus Sequence-binding Protein (ICSBP/IRF8) Represses PTPN13 Gene Transcription in Differentiating Myeloid Cells

Abstract: The interferon consensus sequence-binding protein (ICSBP/ IRF8) is an interferon regulatory factor that is expressed in myeloid and B-cells. ICSBP-deficient mice develop a myeloproliferative disorder characterized by cytokine hypersensitivity and apoptosis resistance. To identify ICSBP target genes involved in these effects, we screened a CpG island microarray with chromatin that co-immunoprecipitated with ICSBP from myeloid cells. Using this technique, we identified PTPN13 as an ICSBP target gene. PTPN13 enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(134 citation statements)
references
References 37 publications
(64 reference statements)
8
126
0
Order By: Relevance
“…This set included genes that terminate cytokine-induced proliferation (NF1 and GAS2), increase sensitivity of phagocytes to Fas-induced apoptosis (PTPN13), and are involved in DNA repair (FANCF) (14)(15)(16)(17). We found that IRF8 activated FANCF (the gene encoding Fanconi F) in bone marrow progenitor cells that were stimulated with differentiating cytokines (17).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…This set included genes that terminate cytokine-induced proliferation (NF1 and GAS2), increase sensitivity of phagocytes to Fas-induced apoptosis (PTPN13), and are involved in DNA repair (FANCF) (14)(15)(16)(17). We found that IRF8 activated FANCF (the gene encoding Fanconi F) in bone marrow progenitor cells that were stimulated with differentiating cytokines (17).…”
Section: Introductionmentioning
confidence: 90%
“…The PCR product was sequenced to assure that no mutations were present. IRF8-specific shRNAs were designed and subcloned into the pLKO expression vector, as previously described (15,16). These shRNAs consistently reduce IRF8 expression in U937 cells by 70% (15,16).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages, monocytes, DCs and T cells from these mice also showed functional abnormalities, with resistance to apoptosis and hypersensitivity to cytokines (Huang, Zhu et al 2008). These defects indicate the importance of IRF8 in myelopoiesis.…”
Section: Interferon Regulatory Factors (Irfs)mentioning
confidence: 94%
“…Specific IRF family members have well-established functions in development of immune cell lineages. IRF8 plays an important role in development of immune cells including macrophages, monocytes, DCs, natural killer (NK) cells, CD4 + and CD8 + T cells , Turcotte, Gauthier et al 2005, Greeneltch, Schneider et al 2007, Huang, Zhu et al 2008). IRF8 knockout mice showed impaired myeloid cell differentiation, and also developed a syndrome similar to human chronic or acute myelogenous leukemia (Holtschke, Lohler et al 1996).…”
Section: Interferon Regulatory Factors (Irfs)mentioning
confidence: 99%